2018
DOI: 10.1136/bmjopen-2017-021119
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between leisure time physical activity, sedentary behaviour and symptoms of depression and anxiety: evidence from a population-based sample of Canadian adolescents

Abstract: BackgroundPhysical and sedentary activities have been identified as potentially modifiable risk factors for many diseases, including mental illness, and may be effective targets for public health policy and intervention. However, the relative contribution of physical activity versus sedentary behaviour to mental health is less clear. This study investigated the cross-sectional association between physical activity, sedentary activity and symptoms of depression and anxiety at age 14–15 in the National Longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
99
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 43 publications
(32 reference statements)
11
99
0
11
Order By: Relevance
“…[1][2][3] Physical exercise can be effective in primary and secondary prevention of chronic diseases (eg, heart disease, stroke, chronic respiratory diseases, cancer, and diabetes), [4][5][6] which are the leading cause of premature death and disability. Numerous studies also confirmed that regular exercise reduces the risk of anxiety and depression, [7][8][9] improves well-being 10,11 and quality of life. [12][13][14] Furthermore, physical activity is indicated as an independent predictor of successful aging.…”
Section: Introductionmentioning
confidence: 85%
“…[1][2][3] Physical exercise can be effective in primary and secondary prevention of chronic diseases (eg, heart disease, stroke, chronic respiratory diseases, cancer, and diabetes), [4][5][6] which are the leading cause of premature death and disability. Numerous studies also confirmed that regular exercise reduces the risk of anxiety and depression, [7][8][9] improves well-being 10,11 and quality of life. [12][13][14] Furthermore, physical activity is indicated as an independent predictor of successful aging.…”
Section: Introductionmentioning
confidence: 85%
“…The nurses who exercise and have higher levels of physical activities are less likely to get depression than the nurses who do not exercise and have low levels of physical activities. Physical inactivity and sedentary behavior are signi cantly associated symptoms of depression and anxiety (33).…”
Section: Discussionmentioning
confidence: 99%
“…It is now established that social isolation must be regarded as a primary public health concern in the elderly, as it amplifies the burden of neurocognitive, mental, cardiovascular and autoimmune problems, as well as depression and anxiety [52]. Moreover, recent evidence has demonstrated that sedentary behaviors in the youth may also be an important cause of depression and anxiety [53]. As such, self-isolation should be seen as a global healthcare and societal issue.…”
Section: Social Isolationmentioning
confidence: 99%